2018
DOI: 10.3847/1538-4357/aaaab1
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Explanations for Extreme Supersolar Iron Abundances Inferred from the Energy Spectrum of Cygnus X-1

Abstract: Here we study a 1-200 keV energy spectrum of the black hole binary Cygnus X-1 taken with NuSTAR and Suzaku. This is the first report of a NuSTAR observation of Cyg X-1 in the intermediate state, and the observation was taken during the part of the binary orbit where absorption due to the companion's stellar wind is minimal. The spectrum includes a multi-temperature thermal disk component, a cutoff power-law component, and relativistic and non-relativistic reflection components. Our initial fits with publicly a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
181
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(201 citation statements)
references
References 66 publications
18
181
2
Order By: Relevance
“…In previous studies, a narrow Fe Kα line, which could be produced in the region far away from the central black hole, was already detected in the X-ray spectra of some black hole X-ray binaries, such as GX 339-4 (García et al 2015) and Cyg X-1 (Tomsick et al 2018).…”
Section: Relativistic Reflection Models For Suzaku and Rxte Spectramentioning
confidence: 88%
See 2 more Smart Citations
“…In previous studies, a narrow Fe Kα line, which could be produced in the region far away from the central black hole, was already detected in the X-ray spectra of some black hole X-ray binaries, such as GX 339-4 (García et al 2015) and Cyg X-1 (Tomsick et al 2018).…”
Section: Relativistic Reflection Models For Suzaku and Rxte Spectramentioning
confidence: 88%
“…Forcing A Fe at the solar abundance in Model 1 will lead to a worse fit (∆ χ 2 ∼156.63 with 1 degree of freedom), but the spin parameter a * is 0.79 +0.06 −0.10 , which still indicates a moderate rotating black hole. We also tried a new version of reflionx model (reflionx_hd) with the electron density as a free parameter (Tomsick et al 2018). The iron abundance is fixed at solar abundance.…”
Section: Relativistic Reflection Models For Suzaku and Rxte Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The most likely explanation is the atomic data shortcomings in current reflection models. Tomsick et al (2018) explored the super-solar iron abun-dance of Cyg X-1 using observation of the intermediate state.…”
Section: Discussionmentioning
confidence: 99%
“…The high density model leads to increasing soft X-ray flux. Recent reflection analyses of Cyg X-1 by Tomsick et al (2018), and GX 339-4 by García et al (2015) and Jiang et al (2019) suggest that reflection models which underestimate the density of disc introduce systematic changes of order 10 • in the inclination angle. Shafee et al (2006) first reported the spin of the black hole in 4U 1543 via the continuum-fitting method.…”
Section: Discussionmentioning
confidence: 99%